Gender Bias Analysis And Right To Fight For Gender Equality In Education Through The Children's Book “I Am Kartini” - Ulfa, Faiza; Mukaromah, Nisaul; Puspitasari, Dewi (Berumpun: International Journal of Social, Politics, and Humanities, 2023)
This study employs visual discourse analysis to reveal the visual elements within the children's book "I AM KARTINI." Its primary objective is to assess how the book conveys the interplay between gender and the pursuit of gender equality, particularly concerning education. The analysis reveals a both the promotion of Gender Equality and the presence of Gender Inequality. "I AM KARTINI" strongly advocates for Gender Equality, emphasizing the critical importance of granting women equal access to education. The book communicates the idea that numerous women recognize education's pivotal role in their lives and society as a whole, championing women's inherent right to the same opportunities enjoyed by men. However, the analysis also uncovers instances of Gender Inequality depicted in the book, connecting patriarchal culture within the Indonesian educational system. The book portrays stereotypes that restrict women to domestic roles, primarily centered on family and household responsibilities. This research highlights the critical importance of examining how gender is represented in children's literature. "I AM KARTINI" serves as a powerful instrument in this endeavor, advocating for gender equality while also highlighting the ongoing challenges related to gender bias and inequality within the Indonesian educational landscape. These findings emphasise the urgent need to recognize and address these issues to foster an inclusive educational environment where every individual has an equal opportunity to thrive.